1985
DOI: 10.1172/jci111875
|View full text |Cite
|
Sign up to set email alerts
|

Use of a murine monoclonal antibody for detection of circulating plasma DF3 antigen levels in breast cancer patients.

Abstract: The murine monoclonal antibody (MAb), designated DF3, reacts with a 300,000-mol wt mammary epithelial antigen. A sequential double-determinant radioimmunoassay (RIA) has been developed to monitor circulating DF3 antigen. Using this assay, we have demonstrated that 33 of 36 normal women had plasma RIA antigen levels < 150 U/mi. In contrast, 33 of 43 patients (76%) with metastatic breast cancer had RIA DF3 antigen levels _ 150 U/ml. The difference between these two groups was statistically significant (P < 0.001… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
68
1
1

Year Published

1986
1986
1999
1999

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(72 citation statements)
references
References 25 publications
2
68
1
1
Order By: Relevance
“…In particular, conditions affecting the liver, pancreas and gastrointestinal system produced elevated levels, however, in general the levels were much lower than those found in active breast cancer. Similar results have been found with other breast cancer markers (Khoo & Mackay, 1973;Hayes et al, 1985). MSA levels were also raised in a substantial number of patients with non-breast tumours; this is not a surprising result given the tissue distribution of the monoclonal antibody 3E1.2 on secretory epithelium (Stacker et al, 1985a).…”
Section: Discussionsupporting
confidence: 85%
See 2 more Smart Citations
“…In particular, conditions affecting the liver, pancreas and gastrointestinal system produced elevated levels, however, in general the levels were much lower than those found in active breast cancer. Similar results have been found with other breast cancer markers (Khoo & Mackay, 1973;Hayes et al, 1985). MSA levels were also raised in a substantial number of patients with non-breast tumours; this is not a surprising result given the tissue distribution of the monoclonal antibody 3E1.2 on secretory epithelium (Stacker et al, 1985a).…”
Section: Discussionsupporting
confidence: 85%
“…MSA levels were also raised in a substantial number of patients with non-breast tumours; this is not a surprising result given the tissue distribution of the monoclonal antibody 3E1.2 on secretory epithelium (Stacker et al, 1985a). Levels (Table I); this has also been reported for the marker DF3 (Hayes et al, 1985). Results of this study have also confirmed that MSA levels would be useful for monitoring the clinical course of breast cancer.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…That 46 Kd molecule is probably distinct from the antigens detected by HMFG1 and HMFG2. Other breast epithelial antigens defined by monoclonal antibodies such as antibody MF3 (Hayes et al, 1985), antibody F36/22 (Papsidero et al, 1984) and antibody 24-17.2 (Thomson et al, 1983) have been detected in increased amounts in the sera of patients with metastatic breast cancer. These assays developed using conventional sandwich techniques appear to be of promise in the monitoring of patients with metastatic disease.…”
Section: Discussionmentioning
confidence: 99%
“…Of clinical interest, it has been reported that PEMs are elevated in the circulation of advanced breast carcinoma patients (Burchell et al, 1984;Hayes et al, 1985;Hilkens et al, 1986;Price et al, 1987) and these findings have promoted investigation into its potential as a prognostic or diagnostic indicator. The present study describes the purification and partial characterisation of PEM isolated from advanced breast carcinoma patients' sera and its use in the production of a second-generation MAb, C568.…”
mentioning
confidence: 99%